The role of covid-19 anxiety and intolerance of uncertainty in predicting resilience - Duru, Yagmur Benian; Gunal, Vuslat; Agaoglu, Ceyda Yalcin; Tatli, Cemre (WILEY)
Resilience is one of the protective factors for mental health. The aim of this study is to reveal the role of COVID-19 anxiety and intolerance of uncertainty in predicting resilience in adulthood. To this end, data were collected from 533 adults (359 women-174 men). A hierarchical regression analysis was performed, controlling for the effects of gender and presence of a chronic disease on the prediction of resilience. Results showed that intolerance of uncertainty and COVID-19 anxiety were statistically significant predictors of resilience. Gender and presence of a chronic disease were not statistically significant in predicting resilience. These results indicate that intolerance of uncertainty plays an important role in explaining resilience.
Keywords: COVID-19 anxiety; intolerance of uncertainty; pandemic; resilience